Penentuan Interval Waktu Preventive Maintenance Mesin Dengan Tindakan Berdasarkan Metode Reliability Centered Maintenance (RCM) Pada PT PLN (Persero) UPK Bukittinggi - Dedi Erawadi; Tri Artono; Ibnul Nanda Rianza; Hendra Hendra; Adriansyah Adriansyah; Abdul Halim (MEDIA PERSPEKTIF : Journal of Technology, 2022)
UPK Bukittinggi is a state electricity company in charge of 3 hydropower plants in West Sumatra with a vision to become the leading electricity company in Southeast Asia. To realize this vision, the company must continue to monitor a good level of productivity on the quality of engine performance which must be maintained. For this reason, it is necessary to propose a preventive maintenance plan for each hydropower plant with actions based on the Reliability Centered Maintenance (RCM) method. The purpose of the study was to calculate the amount of time for repair (Mean Time To Repair) and the amount of time the damage occurred (Mean Time To Failure) as well as determine the maintenance time interval schedule for the equipment experiencing the highest downtime at UPK Bukittinggi. Where the RCM method is integrated with the Failure Mode Effects Analysis (FMEA) method which is used as an analysis of the failure mode that occurs by calculating the highest Risk Priority Number (RPN) value on the machine and then calculating the time interval for damage as the basis for determining the maintenance schedule. The result of the research is that with routine scheduling of machine maintenance will be obtained with time intervals obtained by time intervals and maintenance actions using the RCM method.